Democracy Issue Usage via Website by Radical Group in Opposing Indonesian Government - Karman karman; Djoko Waluyo (BBPSDMP KOMINFO MAKASSAR, 2018)
This article dealt with the issue of how radical groups include Indonesian government as a democratic country, through the practice of language usage in online media. That radical group is Jamaah Ansharu Tauhid (JAT). We collect data from the web page (www.ansharuttauhid.com) with the word of ‘democracy’ in the proses of query. We determine contents containing government representation on democratic issue. We analysed the text with an analysis model of representation of social actors and social action as Theo VanLeeuwen introduced. We conclude that JAT include the Indonesian government as outsiders in the context of religion. The government is different from JAT in the context of religion. JAT delegitimized Indonesian government with some language techniques. JAT symbolized Indonesia government as “thoghut”, and included it in the web contents negatively (e.g., by pseudo title, epithets, etc.). On the contrary, JAT appreciated terrorism perpetrators by harnessing honorification technique. The inclusion and delegitimacy of the Indonesian government depart from religion as an idiosyncratic system of meaning.